Recent Updates in Nanocrystal Technology: A Reference to Oral Drug Delivery System - Magdum, Sonali Vijaykumar; Shirote, Pramodkumar Jaykumar (Micro and Nanosystems, 2025)
Increasing the oral bioavailability of drugs that dissolve slowly may be possible with the use of nanocrystal technology. It is being employed for drug engineering and research after making rapid advancements in recent years. The manufacturing process for pharmaceuticals is significantly hampered by the low solubility and quick rate of dissolution of poorly soluble medications. When taken orally, medications that are poorly soluble often have low and inconsistent bioavailability, which could lead to therapeutic failure. Pure drug nanocrystals prepared via “bottom-up” or “top-down” procedures are able to significantly improve the way poorly soluble medications dissolve thanks to their enormous surface area, which in turn enhances oral absorption. Nanocrystal medications allow for the creation of various dosage formulations. The use of nanocrystal technology in pharmaceutical research, particularly for oral drug delivery systems, is the main focus of this review. First, a quick discussion on the characteristics of pharmaceutical nanocrystals and several nanocrystal technology preparation techniques is provided. The application of nanocrystal technology in pharmaceutical science is covered after a discussion of the creation of prolonged-release formulations. Next follows a brief overview of the scaling-up procedure, commercial nanocrystal drug products, and regulatory aspects of nanodrugs. This paper offers a thorough explanation of preparation techniques, their characterisation, and how they are used in oral drug delivery systems.
Keywords: nanocrystal